2021
DOI: 10.1136/gpsych-2020-100247
|View full text |Cite
|
Sign up to set email alerts
|

Rates and risk factors for suicidal ideation, suicide attempts and suicide deaths in persons with HIV: a systematic review and meta-analysis

Abstract: BackgroundPeople living with HIV/AIDS (PLWHA) must contend with a significant burden of disease. However, current studies of this demographic have yielded wide variations in the incidence of suicidality (defined as suicidal ideation, suicide attempt and suicide deaths).AimsThis systematic review and meta-analysis aimed to assess the lifetime incidence and prevalence of suicidality in PLWHA.MethodsPublications were identified from PubMed (MEDLINE), SCOPUS, OVID (MEDLINE), Joanna Briggs Institute EBP and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 65 publications
5
39
0
1
Order By: Relevance
“…According to this study's findings, the prevalence of suicidal ideation among PLHIV within the included studies was 22.3%. This result was consistent to that obtained in a recent systematic review and meta-analysis based on studies in Africa on persons with HIV/AIDS that reported the prevalence of suicidal ideation as 21.7% (66) and 22.8% according to a study conducted by Pelton et al (16). However, the results of the present study were lower than those of a meta-analysis that showed that approximately 19.6% of young people with HIV/AIDS had lifetime suicidal ideation and that the global prevalence of suicidal ideation was 24.38% during the study period (67).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to this study's findings, the prevalence of suicidal ideation among PLHIV within the included studies was 22.3%. This result was consistent to that obtained in a recent systematic review and meta-analysis based on studies in Africa on persons with HIV/AIDS that reported the prevalence of suicidal ideation as 21.7% (66) and 22.8% according to a study conducted by Pelton et al (16). However, the results of the present study were lower than those of a meta-analysis that showed that approximately 19.6% of young people with HIV/AIDS had lifetime suicidal ideation and that the global prevalence of suicidal ideation was 24.38% during the study period (67).…”
Section: Discussionsupporting
confidence: 92%
“…Also, our included suicide-related studies in this review are cross-sectional studies. Furthermore, a long-term observational study or database analysis is recommended for future studies ( 16 , 42 , 43 ). Third, we assessed the pooled prevalence of suicidal behaviors, including suicidal ideation, suicide attempts, and suicides, as well as risk factors associated with each behavior for PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis showed that the risk of successful suicide in HIV-infected individuals was 100-fold that of the general population. HIV progression (AIDS) may be associated with this increased risk of suicide through the direct effects of a high viral load on the brain and HAART, and a high level of CD4 was associated with decreased level of suicidal attempts [ 28 ]. The stigma and physiological effects of HAART could affect personal relationships and may also be associated with suicidal ideation or attempts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV progression (AIDS) may be associated with this increased risk of suicide through the direct effects of a high viral load on the brain and HAART, and a high level of CD4 was associated with decreased level of suicidal attempts [ 28 ]. The stigma and physiological effects of HAART could affect personal relationships and may also be associated with suicidal ideation or attempts [ 28 ]. Thus, routine suicide risk assessment, psychological counseling, and mental health care should be included in the HIV treatment plan, which currently focuses on HAART to decrease the viral load and increase CD4 counts.…”
Section: Discussionmentioning
confidence: 99%
“…Although suicidality is a serious problem among PLWH, few studies have focused on suicide death, suicide attempt (SA), and suicidal ideation (SI) in this population (5). Worldwide, the incidence of suicide death and lifetime prevalence of SA and SI were substantially higher in PLWH than in the general population (6). In China, among PLWH, suicide is one of the leading causes of non-AIDS death (7).…”
Section: Introductionmentioning
confidence: 99%